2015
DOI: 10.1007/s10495-015-1120-6
|View full text |Cite
|
Sign up to set email alerts
|

Apoptin interacts with and regulates the activity of protein kinase C beta in cancer cells

Abstract: Apoptin, the VP3 protein from chicken anaemia virus (CAV), induces tumour cell-specific cell death and represents a potential future anti-cancer therapeutic. In tumour but not in normal cells, Apoptin is phosphorylated and translocates to the nucleus, enabling its cytotoxic activity. Recently, the β isozyme of protein kinase C (PKCβ) was shown to phosphorylate Apoptin in multiple myeloma cell lines. However, the exact mechanism and nature of interaction between PKCβ and Apoptin remain unclear. Here we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 39 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…To further evaluating the effectiveness of a potential delivery tool hPP10 for other macromolecules, GFP and Apoptin were conjugated with the C-terminal fragment of hPP10 separately, and their fusion protein produced using prokaryotic expression systems, then we directly visualized the well-distributed in cellular of these conjugated protein. Furthermore, we evaluated the function of these cargo, including the apoptosis induction by Apoptin, although the exact mechanism of apoptosis induced by Apoptin remains obscure [56]. Apoptin fused with hPP10 penetrate into cytoplasm and induce the cancer cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…To further evaluating the effectiveness of a potential delivery tool hPP10 for other macromolecules, GFP and Apoptin were conjugated with the C-terminal fragment of hPP10 separately, and their fusion protein produced using prokaryotic expression systems, then we directly visualized the well-distributed in cellular of these conjugated protein. Furthermore, we evaluated the function of these cargo, including the apoptosis induction by Apoptin, although the exact mechanism of apoptosis induced by Apoptin remains obscure [56]. Apoptin fused with hPP10 penetrate into cytoplasm and induce the cancer cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptin is known to bind multiple partners including Hippi [ 22 , 23 ], APC1 [ 23 ], HSP70 [ 24 ], Crm1 protein for nuclear export [ 17 ], Bcr-Abl oncoprotein [ 20 ], p85 subunit of PI3-Kinase [ 25 , 26 ], DEDAF (human death effector domain-associated factor) [ 27 ], FADD, Bcl 10 [ 52 ], and PKC (protein kinase C) beta [ 39 ]. Recent studies have shown that apoptin inhibits Bcr-Abl1 kinases in chronic myeloid leukemia (CML), and regulates the activity of protein kinase C (PKC) in myeloma cell lines, respectively [ 39 , 40 ]. However, none of these proteins have demonstrated a conserved interaction motif, although the larger SH3 domain of Bcr-Abl1 and PI3-Kinase appear to be involved [ 20 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…While many reports suggest that cancer cells differentially express a kinase that phosphorylates Apoptin at T108 thereby activating it, the nature and identity of such a kinase have remained an enigma. Protein kinase C (PKC), cyclin-dependent kinases (CDKs) 1 and 2, homeodomain-interacting protein kinase 2 (HIPK2), phosphoinositide 3-kinase (PI3K), and checkpoint kinases (Chk) are some of the kinases that have been incriminated in Apoptin activation ( Los et al, 2009 ; Maddika et al, 2009 ; Kucharski et al, 2011 , 2016 ; Zhao et al, 2013 ; Bullenkamp et al, 2015 ).…”
Section: Mechanism Of Actionmentioning
confidence: 99%